Mistisme Islam: Membincang Epistemologi Kaum Sufi - Zainuddin Puteh; M. Iqbal Irham; Sugeng Wanto (IAIN Bengkulu, 2022)
The spiritual emptiness of modern humans stems from the epistemology of Western positivism, which fails to fulfill its promise to bring humans to a happy standard of living. Therefore, it is necessary to study alternative epistemology for future knowledge for the sake of human happiness itself. As a mystical science in Islam, Sufism invites people to directly absorb knowledge from the